Comparison of bulk and microfluidic methods to monitor the phase behaviour of nanoparticles during digestion of lipid-based drug formulations using in situ X-ray scattering - Hong, Linda; Sesen, Muhsincan; Hawley, Adrian; Neild, Adrian; Spicer, Patrick T.; Boyd, Ben J. (Soft matter, 2019)
The performance of orally administered lipid-based drug formulations is crucially dependent on digestion, and understanding the colloidal structures formed during digestion is necessary for rational formulation design. Previous studies using the established bulk pH-stat approach (Hong et al. 2015), coupled to synchrotron small angle X-ray scattering (SAXS), have begun to shed light on this subject. Such studies of digestion using in situ SAXS measurements are complex and have limitations regarding the resolution of intermediate structures. Using a microfluidic device, the digestion of lipid systems may be monitored with far better control over the mixing of the components and the application of enzyme, thereby elucidating a finer understanding of the structural progression of these lipid systems. This work compares a simple T-junction microcapillary device and a custom-built microfluidic chip featuring hydrodynamic flow focusing, with an equivalent experiment with the full scale pH-stat approach. Both microfluidic devices were found to be suitable for in situ SAXS measurements in tracking the kinetics with improved time and signal sensitivity compared to other microfluidic devices studying similar lipid-based systems, and producing more consistent and controllable structural transformations. Particle sizing of the nanoparticles produced in the microfluidic devices were more consistent than the pH-stat approach.